Evidence summary of meaning in life intervention for cancer patients - Yuan, Ping; Lu, Weinan; Yong, Xia; Yang, Wenli; Zhong, Xiaoying; Wang, Meng; Zhang, Yiying; Fang, Ting; Xie, Yan; Li, Xuemei; Zhang, Limei (Frontiers in Oncology, 2025)
ObjectiveTo evaluate and summarize evidence on intervention of the meaning of life of cancer patients, and provide evidence-based basis for clinical practice.MethodsAccording to the “6S” evidence model, The literature related to the life meaning intervention in cancer patients were systematically searched in domestic and foreign evidence-based resource databases,comprehensive databases and professional society websites from the inception of database to Oct 2023. Two researchers evaluated the quality of the literature, extracted and integrated evidence.ResultsA total of 28 articles were included, including 2 the computer decisions, 4 guidelines, 7 systematic evaluations, 6 quasi-experimental studies, and 9 randomized controlled trials. A final total of 48 pieces of evidence were summarized, including 5 areas of organizational management, assessment, evaluation indicators, intervention programs for meaning of life, and intervention techniques.ConclusionThis study forms the evidence of intervention of the meaning of life of cancer patients, which can provide reference for clinical practice, Individualized treatment and nursing care should be provided according to the symptoms and actual needs of the patients, and relevant evidence should be updated in time.